Design and synthesis of new 1,2,4-oxadiazole/quinazoline-4-one hybrids with antiproliferative activity as multitargeted inhibitors - Mohamed, Amira M.; Abou-Ghadir, Ola M. F.; Mostafa, Yaser A.; Dahlous, Kholood A.; Bräse, Stefan; Youssif, Bahaa G. M. (Frontiers in Chemistry, 2024)
A novel series of 1,2,4-oxadiazole/quinazoline-4-one hybrids was developed as antiproliferative multitargeted inhibitors. 9a-o were tested as antiproliferative agents. The results showed that the majority of the tested compounds showed significant antiproliferative action with 9b, 9c, 9h, 9k, and 9l being the most potent. Compounds 9b, 9c, 9h, 9k, and 9l were tested as EGFR and BRAF V600E inhibitors. These in vitro tests revealed that compounds 9b, 9c, and 9h are strong antiproliferative agents that may act as dual EGFR/BRAF V600E inhibitors. 9b, 9c, and 9h were further investigated for their inhibitory effect on mutant EGFR (EGFR T790M ), and the results showed that the tested compounds had considerable inhibitory action. Cell cycle study and apoptosis detection demonstrated that compound 9b exhibits cell cycle arrest at the G2/M transition. Molecular docking simulations reveal the binding mechanism of the most active antiproliferative agents.